Pengaruh kepemimpinan transformasional, learning organization, dan komitmen organisasi terhadap kinerja dosen - Evyria Mauline Natiur Hutapea (FORUM EKONOMI, 2016)
This study is expected to explore the elements that can affect the performance of employees one of which the performance of lecturers in Universities by increasing commitment within the organization and have a sense of pride as part of a learning organization, and improve transformational leadership in the community and learning in Indonesia. The research method that will be implemented is to undertake surveys using path analysis. How To gather the necessary data in this study is the use of questionnaires and tests that have been prepared beforehand. This study will examine the relationship between the variables, and measure the effect of one variable to another variable. Tentative conclusions on the results of the study were a group of lecturers who continue to expand their capacity to create, manage and use knowledge for their desired result can be scalable development of science, the development of communication, may collaborate with others, and can utilize the knowledge learning organization in the work and can utilize technology.Keyword: Transformational Leadership, Learning Organization, Organizational Commitment, and Performance